Does the position of external branch of superior laryngeal nerve change with the height of the patients and the length of the larynx - Senanayake, K. J.; Fernando, R.; Salgado, S.; Jayanthi, M. (Jaypee Publisher, 2012)
When the external branch of superior laryngeal nerve (EBSLN) crosses the superior thyroid artery closer to thyroid upper pole, the EBSLN has a higher risk of getting damaged. Its anatomical position in relation to thyroid upper pole may vary with changing the height of patient and the length of larynx. We intended to test this hypothesis and predict the risk. Thirty cadavers of both sexes are dissected (29-87 years, mean 69). One cadaver excluded due to a goiter and five nerves were damaged during dissection. Therefore, 53 nerves were studied. The distance from upper pole of thyroid to the point where the nerve crosses the superior thyroid artery (TS) was measured. Cadaver length (CL), cricothyroid length (CT) and the cricohyoid length (CH) measured to the closest millimeter. Correlation of TS with CL, CT and CH was measured. The mean distance from the upper pole of the thyroid to the point where EBSLN crosses superior thyroid artery was 6.24 mm (SD 5.94). On right side, the mean distance was 4.03 mm (SD 5.34) and, on the left, 8.37 mm (SD 5.7 mm). The difference between two means was significant at 0.05 (t = 2.82, p = 0.007). There was a strong correlation between distance from the upper pole of the thyroid to the point where the nerve crosses the superior thyroid artery with CL (r = 0.98). There was moderate correlation with the CT and CH lengths (r = 0.55, 0.58 respectively). The position of EBSLN in relation to thyroid upper pole is strongly correlated with the height of the patient. The EBSLN crosses superior thyroid artery more closely to thyroid upper pole in right side.
Indexed in Scopus; EMBASE, Not in PUBMED/MEDLINE
Keywords: External branch superior Laryngeal nerve; Thyroidectomy